2006
DOI: 10.1001/archinte.166.19.2065
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Guideline for Venous Thromboembolism Prophylaxis in Elderly Post–Acute Care Patients

Abstract: A multifaceted intervention addressing venous thromboembolism prophylaxis in post-acute care patients can be followed by a significant decrease in the rate of any DVT in elderly patients. More active interventions are needed to enforce compliance with evidence-based guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…22 We should note that the isolated increase in use of compression stockings was also seen in studies following the implementation of protocols to improve thromboprophylaxis performed elsewhere. 25,35 Even taking in consideration the degree of anti-thrombotic protection provided by graduated elastic compression stockings, 36,37 the results of implementing the protocol still leave much to be desired, since this method was often used for too short a period when compared to patients' total length of stay. The absence of more effective results from implementing the DVT protocol at the two HSL Admission Units may be connected to the lack of continuous advertisement of prophylaxis guidelines, though at first HSL's Clinical Staff was firmly mobilized, and a communications campaign publicized the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…22 We should note that the isolated increase in use of compression stockings was also seen in studies following the implementation of protocols to improve thromboprophylaxis performed elsewhere. 25,35 Even taking in consideration the degree of anti-thrombotic protection provided by graduated elastic compression stockings, 36,37 the results of implementing the protocol still leave much to be desired, since this method was often used for too short a period when compared to patients' total length of stay. The absence of more effective results from implementing the DVT protocol at the two HSL Admission Units may be connected to the lack of continuous advertisement of prophylaxis guidelines, though at first HSL's Clinical Staff was firmly mobilized, and a communications campaign publicized the guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of evidence-based prevention guidelines for VTE, prophylaxis of VTE has been underused or often inappropriately used for all patients at risk (Cohen et al, 2008;Jaffer et al, 2008;Sellier et al, 2006;Yu et al, 2007). Very few studies have looked at VTE prevention focusing on the older population.…”
Section: Vte Prevention and Management In The Older Adult Populationmentioning
confidence: 99%
“…Very few studies have looked at VTE prevention focusing on the older population. A recent multicenter study (Sellier et al, 2006) was conducted to determine whether a multifaceted intervention, including pharmacological and mechanical prophylaxis, decreased the incidence of DVT in elderly post-acute care patients. The results from Sellier et al's (2006) study showed that DVT occurred in 12% of older adults during the preintervention phase and 8% during the postintervention phase (p = 0.002).…”
Section: Vte Prevention and Management In The Older Adult Populationmentioning
confidence: 99%
See 2 more Smart Citations